Upaya Meningkatkan Kekuatan Otot dengan Dukungan Mobilisasi Latihan Range of Motion (RoM) Aktif dan Pasif pada Pasien Stroke Non Hemoragik: Literature Review - Septiana, Anggita; Febriarini, Nurul Isnaini; Octavianugrah, Kintel Edy (Jurnal Keperawatan Sehat Mandiri, 2023)
Non-hemorrhagic stroke is a manifestation of systemic disease in the elderly in the form of impaired blood circulation to the brain which causes neurologic deficits, which requires appropriate nursing intervention such as active and passive Range of Motion (ROM) joint strengthening exercise techniques to increase muscle strength. Objective: To identify research journals regarding factors that influence the effectiveness of efforts to increase muscle strength with the support of active and passive Range of Motion (ROM) mobilization exercises in non-hemorrhagic stroke patients. Research Method: This research is a literature review research by searching for journals through ProQuest, GARUDA, and Pubmed which discuss active and passive Range of Motion (ROM) procedures in non-hemorrhagic stroke patients. Research Results: The results of the literature review of active and passive Range of Motion (ROM) nursing actions in non-hemorrhagic strokes generally have an influence before and after the action is given by paying attention to various factors that influence the effectiveness of increasing muscle strength. This is relevant to the author's case, namely Mr. NW, who experienced an increase in muscle strength because he paid attention to the time factor of the duration of the action which was continued systematically. Conclusion: From the results of the literature review and cases managed by the author, it can be concluded that efforts to increase muscle strength in non-hemorrhagic stroke patients can be increased with active and passive Range of Motion (ROM) nursing actions but by paying attention to various factors that influence the effectiveness of increasing muscle strength such as the duration factor. providing action, patient factors (level of awareness and self-motivation), and family support factors